Reaction Mechanism and Structural Evolution of Tunnel‐Structured KCu7S4 Nanowires in Li+/Na+‐Ion Batteries - Zhang, Kuikui; Wang, Hui; Du, Xiaobing; Dai, Shuge; Wang, Ye; Xu, Tingting; Liu, Meilin; Cheng, Shaobo (Advanced functional materials, 2024)
Selecting suitable electrode materials for sodium‐ion batteries (SIBs) often relies on the experience gained from lithium‐ion batteries (LIBs), particularly in terms of thermodynamics. However, this approach may fall into a stagnant situation where the development of SIBs consistently lags behind that of LIBs due to the larger ionic radius of Na+. Accordingly, it is crucial to establish a dedicated selection rule specifically tailored for SIB electrodes to overcome this challenge. Herein, a screening method is proposed for SIB materials, where an ideal candidate shall form a stable intermediate transition phase with Na+. This phase acts as an important bridge that can regulate the insertion/extraction of charge carriers. Atomically resolved transmission electron microscopy demonstrates that KCu7S4 can react with Na+ to form a stable intermediate phase (Na3Cu4S4). Na3Cu4S4 can undergo reversible conversion reactions, contribute capacity, stabilize the tunnel structure and enhance the migration/diffusion of Na+. In contrast, Li+ can't form a stable intermediate phase in KCu7S4 during lithiation/delithiation, thus losing the ability to effectively regulate Li+ insertion/extraction. These findings provide valuable insights for the development of suitable electrode materials for SIBs, emphasizing the importance of stable intermediate phases in regulating charge carrier insertion/extraction and improving overall battery performance. This work systematically investigates the electrochemical properties, reaction kinetics, and detailed structural evolution of KCu7S4 during Li+/Na+ insertion/extraction by using (S)TEM at the atomic scale and DFT calculations. The study provides valuable insights into understanding the ionic‐scale migration mechanism and the structure‐property relationship of transition metal sulfides in rechargeable ion batteries.